“Green Hotel”: Concepts and Implementation - ILINA, Elena L.; MILORADOV, Konstantin A.; KOVALTCHUK, Andrey P. (Journal of Environmental Management and Tourism; Vol 10 No 2 (2019): JEMT VOlume X Issue 2(34) Spring 2019, 2019)
The authors analyzed the development of the “green hotel” concept, economic and environmental factors affecting the implementation of the “green hotel” concept, proposed an approach to the implementation of the “green hotel” concept, taking into account the regional specifics of the Russian hospitality market.